Concomitant Unilateral Duane Retraction Syndrome and Contralateral Brown's Syndrome. Issue 1 (2nd January 2023) - Mirmohammadsadeghi, Arash; Akbari, Mohammad Reza; Soltani Shahgholi, Sahel
ABSTRACT: A 10-year-old boy was introduced with a chief complaint of ocular misalignment from birth. Ocular examination indicated right Brown and left Duane retraction syndrome in a non-familial pattern. We suspect that a teratogenic damage or genetic mutation may be responsible for this combination.